The role of the basal ganglia and cerebellum in adaptation to others' speech rate and rhythm: A study of patients with Parkinson's disease and cerebellar degeneration. (December 2022) - Späth, Mona; Aichert, Ingrid; Timmann, Dagmar; Ceballos-Baumann, Andrés O.; Wagner-Sonntag, Edith; Ziegler, Wolfram
Abstract: Background: Spoken language is constantly undergoing change: Speakers within and across social and regional groups influence each other's speech, leading to the emergence and drifts of accents in a language. These processes are driven by mutual unintentional imitation of the phonetic details of others' speech in conversational interactions, suggesting that continuous auditory-motor adaptation takes place in interactive language use and plasticity of auditory-motor representations of speech persists across the lifespan. The brain mechanisms underlying this large-scale social-linguistic behavior are still poorly understood. Research aim: To investigate the role of cerebellar and basal ganglia dysfunctions in unintended adaptation to the speech rhythm and articulation rate of a second speaker. Methods: Twelve patients with spinocerebellar ataxia type 6 (SCA6), 15 patients with Parkinson's disease (PD), and 27 neurologically healthy controls (CTRL) participated in two interactive speech tasks, i.e., sentence repetition and "turn-taking" (i.e., dyadic interaction with sentences produced by a model speaker). Production of scripted sentences was used as a control task. Two types of sentence rhythm were distinguished, i.e., regular and irregular, and model speech rate was manipulated in 12 steps between 2.9 and 4.0 syllables per second. Acoustic analyses of the participants' utterances were performed to determine the extent to which participants adapted their speech rate and rhythm to the model. Results: Neurologically healthy speakers showed significant adaptation of rate in all conditions, and of rhythm in the repetition task and partly also the turn-taking task. Patients with PD showed a stronger propensity to adapt than the controls. In contrast, the patients with cerebellar degeneration were largely insensitive to the model speaker's rate and rhythm. Contrary to expectations, sentences with an irregular speech rhythm exerted a stronger adaptive attraction than regular sentences in the two patient groups. Conclusions: Cerebellar degeneration inhibits the propensity to covertly adapt to others' speech. Striatal dysfunction in Parkinson's disease spares or even promotes the tendency to accommodate to other speakers' speech rate and rhythm.